2007
DOI: 10.1111/j.1365-2621.2006.01222.x
|View full text |Cite
|
Sign up to set email alerts
|

Garlic extract plus sodium metabisulphite enhances shelf life of ripe banana fruit

Abstract: Ripe banana fruits were subjected to dip treatment for 4 h using chemicals, plant extracts or their combinations, and shelf life of treated fruits stored at room temperature was monitored by assaying fruit firmness. The treatment of fruit with 1% garlic clove extract or 10% onion bulb extract and adjusting the pH to 4.5 extended the shelf life by 4-5 days when compared with untreated fruit. Treatment with a combination of 1% garlic extract and 1 mm sodium metabisulphite and adjusting the pH to 4.5 prolonged th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
8
0

Year Published

2009
2009
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 28 publications
1
8
0
Order By: Relevance
“…Explanations for the lack of softening in propylenetreated rin (E8/PG) fruits indicated the possibility that perhaps insufficient levels of PG enzyme were generated by expression of the E8-PG chimeric gene. Sanwal and Payasi (2007) observed that delay in fruit softening in bananas on treatment with garlic plus sodium metabisulphite extract was accompanied by slowing of the rate of pectin degradation. This was accomplished by the delay in the rate of increase in the activity of the enzyme involved in this process, namely PG.…”
Section: Polygalacturonasementioning
confidence: 95%
See 1 more Smart Citation
“…Explanations for the lack of softening in propylenetreated rin (E8/PG) fruits indicated the possibility that perhaps insufficient levels of PG enzyme were generated by expression of the E8-PG chimeric gene. Sanwal and Payasi (2007) observed that delay in fruit softening in bananas on treatment with garlic plus sodium metabisulphite extract was accompanied by slowing of the rate of pectin degradation. This was accomplished by the delay in the rate of increase in the activity of the enzyme involved in this process, namely PG.…”
Section: Polygalacturonasementioning
confidence: 95%
“…Kojima et al (1994) suggested the coordinated degradation of pectic and hemicellulosic polysaccharides and starch to be the main cause for the pulp softening process. Sanwal and Payasi (2007) further observed starch content to decrease progressively throughout the postclimacteric ripening of banana fruit. The decrease in starch content was accompanied by the increase in soluble sugars.…”
Section: Starch Metabolism During Softeningmentioning
confidence: 99%
“…Some of these extracts also have antifungal activity against pathogens attacking other fresh produce. This was the case of garlic extracts on apples (Daniel et al, 2015) and bananas (Sanwal and Payasi, 2007), or pomegranate extracts on sweet cherries (Li Destri Nicosia et al, 2016), table grapes (Romeo et al, 2015), and potato tubers (Elsherbiny et al, 2016). In the case of stone fruits, plant extracts with activity against Monilinia spp.…”
Section: Plant Extractsmentioning
confidence: 99%
“…Thus, a decline in starch content is accompanied by an increase in soluble sugar content in the fruits. An increase in activity of the enzyme amylase has been implicated in the degradation of starch to sugars and subsequent fruit‐ripening in banana and other starch‐containing fruits (Sanwal and Payasi ). In South Africa, the cultivation of commercial banana varieties is well coordinated in the processes of maturity indices, harvesting, and postharvest treatment to meet export and local standards.…”
Section: Maturity Indices Harvesting and Postharvest Treatmentmentioning
confidence: 99%